Comparative evaluation of decontamination processes for mitigating profenofos residues in chili (Capsicum annuum) - Komal Rawat; Anjana Srivastava; Shishir Tandon; Gajanpal Singh (Current Horticulture, 2025)
A study to assess the eﬃcacy of ten decontamination processes in reducing the pesticide residue load of profenofos from chili (Capsicum annuum L.) was undertaken at College of Basic Science and Humanities, G. B. Pant University of Agriculture and Technology, Pantnagar, during September 2022 to April 2023. The extraction of insecticide from chili was initiated after 48 hr of pesticide formulation spray and was done using the QuEChERS (quick, easy, cheap, eﬀective, rugged, and safe) method. The study included a control treatment too in which the pesticide residues were extracted without following any decontamination procedure. The quantitative analysis of insecticide was done by coupled gas chromatography–electron capture detection. The results depicted reduction of pesticide residues in all decontamination treatments compared with the control. Solutions of 1% NaCl and soaking in lukewarm water served as eﬃcient decontaminants for removal (up to 90%) of profenophos residues from chili. Among commercially available decontamination products, soaking in nimwash solution showed remarkable eﬀectiveness followed by veggie clean and Arka Herbiwash.